(untitled) (Raparin Journal of Humanities (RJH), 2020)
Abu-torab Khosravi has obtained a special place among the third generation of Iranian fiction writers through writing a collection of stories under the title of Havieh and Divan-e-Soomanat and two novels titled Asfar-e-Kateban and Rood-e-Ravi. Despite his precision and attempt at processing a coherence among language, narration and themes, his stories have been, to some extent, neglected due to the narrative complexities and technical nicety in his works. His novel, Asfar-e-Kateban, can be an appropriate selection for explaining the artistry and value of Abu-torab Khosravi. Thus, this novel will be analyzed in terms of structuralism. This novel consists of 12 sequences which contain another three narratives; the proposed subjects and thoughts correspond with its deep-structure, that is to say, the subversion of time.